2018
DOI: 10.3390/ijerph15010110
|View full text |Cite
|
Sign up to set email alerts
|

STI Knowledge in Berlin Adolescents

Abstract: Sexually transmitted infections (STIs) pose a significant threat to individual and public health. They disproportionately affect adolescents and young adults. In a cross-sectional study, we assessed self-rated and factual STI knowledge in a sample of 9th graders in 13 secondary schools in Berlin, Germany. Differences by age, gender, migrant background, and school type were quantified using bivariate and multivariable analyses. A total of 1177 students in 61 classes participated. The mean age was 14.6 (SD = 0.7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 56 publications
(58 reference statements)
6
35
0
5
Order By: Relevance
“…Moreover, nearly (26.1%) of South Africans were aware of a vaccine for HPV prevention, lower knowledge rate (10.8%, N = 1,177) was reported in Berlin, Germany recently (2018). However, the fact that the later study was conducted among students and young adults is needed to beconsidered when comparing the results [114,115].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nearly (26.1%) of South Africans were aware of a vaccine for HPV prevention, lower knowledge rate (10.8%, N = 1,177) was reported in Berlin, Germany recently (2018). However, the fact that the later study was conducted among students and young adults is needed to beconsidered when comparing the results [114,115].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that the later study was conducted among students and young adults is needed to considered when comparing the results. [114,115] .…”
Section: Discussionmentioning
confidence: 99%
“…Female participants showed a significantly higher mean of STDs-KS compared to males (8.51 ± 4.14 vs. 7.32 ± 4.38, p < 0.0001) (see Table 2, Figures 1 and 2). Median (interquartile range) for STDs-KS was 8 (5)(6)(7)(8)(9)(10)(11). Analysis indicates that the type of program in which the participant was registered, and gender, have a significant influence on the STDs-KS (p < 0.0001).…”
Section: Knowledge Of Sexually Transmitted Diseasementioning
confidence: 99%
“…Moreover, the World Health Organization emphasizes the value of knowledge and awareness of the population, as this promotes a drop in the rate of STD incidences and prevalence in the long-run [2]. Research indicates overall low levels of awareness and knowledge of STDs among people in Europe, Africa, and the Middle East; however, evidence from previous research suggests that the majority of people showed the highest awareness and knowledge of AIDS compared to another STDs [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%